Os dias contados: o artista terminal, a pandemia oitentista e o anúncio da contemporaneidade - José Roberto Schneedorf Ferreira da Silva (2023)
During and from the 1980’s provoke onwards, an artworks significant collection was produced under the HIV/AIDS crisis impact, with the pandemic exponentiation as a motive and statement, considered the large quota of artists surprised by the their own diagnosis at the disease first waves. Which meant first losses, due to the absolute lethality, conclusive to an impressive physical deterioration, inclined to public calvary. The creative overcoming as well as the creator persistence, in such circumstances, projects original models of visual discourse to contemporaneity practices, inscribed in the first person singular or plural, and emulated by urgency and remembrance senses, testamentary as well as testimonial. Some part combative, some affective; often both at the same time. The art immediate reaction to the virus that kidnaps it is divided: on the one hand, unprecedented productions are raised with a sense of self-grief, enabling farewell, affection and plastic autobiography as full productive matrices for the art reading, with autofiction as an integral aspect, expressed through a process here supported as a kind of disruption basis, or even art grounds, languages and visibilities expansion methods for confessional writing, for the intimate letter – which becomes, in addition to being public, also being visual arts, graphics and scenic performances. On the other hand, collective articulations of art exhibition’ production, insertion and circulation are renewed, aimed at communal self-support, at public attention and at resistance to regulatory agents of possible subsistence. Taking both prospective sources, and its combinations, the statement will be formulate from the connections between the artworks and the reports of the artists' experiences, when mutually contaminated. And of these with the historical reference period, which in all its clinchers bequeathed to us: historical, cultural, economic, visual, sensorial – as will be proved on a conceptual basting way. Also formal as well: merging with the theoretical system, and basting on it, these artists and those facts, this subjects and those objects, as if they were scraps for a patchwork quilt. Or if they provide sequentassociation blocks, by some cut up method, carrying generational and/or exercisable icons and iconographies, like the Culture Wars and the Sexual Wars; like Jacob Scriptures, with his angel and their times advance announcements; like obvious inspiration figures to the 1980’s, especially the poet Arthur Rimbaud and the writer William Burroughs; and like the reproducible prints, the good piracy, the art/life performance skills and approaches, the photographic and videocaptures; among other compared structures, between viral oratory and organic virality. Of all this fertile data set, all this recuperative and celebratory scope of an intense period, markedly patrimonial for current art, highlight out the plural idea of territoriality, both in its geographical and ideological senses: the place losses, the place escapes, the place convergences, the place creations. From those of the body to those of customs, due to globalization, those days, when counted by their own beings, toldt he most varied retreat sorts.